PREFERENSI PETANI DALAM PENJUALAN GABAH PASCA PANEN DI DESA SUMUR MATI KECAMATAN SUMBERASIH KABUPATEN PROBOLINGGO - Musyarofah Musyarofah; Pudjo Suharso; Titin Kartini (Economic Education, University of Jember, 2017)
This research was conducted to describe farmer preference in post-harvest grain sales and to know the working relationship of farmers with Bulog, middlemen and market kiosk traders. The type of this research is descriptive with qualitative approach. The method of determining the location of research using the method of purposive area is in the Sumur Mati Village Sumberasih District Probolinggo. The main informants in this study were 12 rice farmers, with the criteria of ever selling grain more than 5 times. While the additional informants in this study are Bulog Officials, Brokers, and Kiosk Traders. Data collection methods used consisted of methods: interviews, observation, and documents. Data analysis used is descriptive analysis which include data reduction, data presentation, and conclusion (verification). The results showed that Farmers' preferences in the Sumur Village died based on experience gained and trust decreased. Farmers in Sumur Mati Village sell grain to Bulog, middlemen, and market stall traders. Bulog's relationship with farmers is a partnership. The partnership between Bulog and the farmers did not last long because the farmers felt the loss. The relationship between middlemen and farmers is intertwined in a patron-client bond. A middleman as a patron takes a strategic role in this client's patron relationship by lending money to farmers or clients to meet initial capital requirements. While the relationship between market stall traders with farmers is the relationship between agents and actors as in the theory of Giddens structure. Where the relationship between buying and selling kiosk vendors with farmers in this study also occurs continuously and in it there are social practices. Farmers and traders established contractual relationship